Quantitative Traits of Bayang Ducks Raised with Intensive and Extensive Systems in Bayang District, West Sumatra - Suhartati, Linda; Arlina, Firda; Reski, Sepri (Andalasian Livestock, 2024)
This study aims to determine the polymorphism of quantitative traits of Bayang ducks raised with intensive and extensive system in Bayang District, West Sumatera. This study used 114 Bayang ducks consisting of 60 males and 54 females. Ducks are raised intensively and extensively or traditionally in Bayang District. This study used the observation method by calculating the mean, standar deviation, and coefficient of variation. Data were analyzed using the t-test to see the effect of sex and rearing system. The variables observed in this study were body weight (BW), chest circumference (CC), beak length (BL), wing bone length (WBL), shank length (SL), shank circumference (SC), femur length (FL), tibia length (TL), and Back Length (BAL). The results showed that sex had a significant effect (P<0.01) on FL and (P<0.05) on SL and CC. The rearing system had a significant effect (P<0.05) on SC and FL in male Bayang ducks. The coefficient of variation (CV) in male Bayang ducks was moderate (>5-15%) except for TL which was small (<5%). While in female Bayang ducks WBL and TL have CV classified as low, CC classified as high and other traits classified as medium. The conclusion of this study is that sex and rearing system affect the quantitative characteristics of Bayang ducks and the CV of Bayang ducks is low to high.